Academic Leaders and Decision Making - Dean (Dino) J. Laury Dr. (Academic Chairpersons Conference Proceedings, 2019)
Presenter and participants will discuss decision-making strategies and best practices available to chairs (new or veterans) to support the decision-making process within department operations that are reasonable and meaningful to the department culture.
Keywords: decision theory; decision analysis; decision making